Produção de adsorvente de baixo custo a partir de lodo de esgoto para remoção de corante de efluente têxtil - Pereira, Izadora Consalter (2015)
The large amount of generated sewage sludge is a much larger issue, mainly related to final disposal of this waste. A concern related to wastewater generated in largecquantities is tailor them to discharge standards established in environmental legislation, since they may contain substances which, in large quantities, can cause harmful effects to health and the environment. Apart from that, the presence of dyes in wastewater can cause environmental impacts to water body receptor, changing water quality and jeopardizing the development of organisms in the aquatic environment. The effluents containing dyes have great difficulty being treated. A process that has highlighted in the treatment of these effluents is adsorption. Regarding the problem mentioned involving the huge amount of available sewage sludge and pollution caused by wastewater contaminated with dyes, this study aimed to use of sewage sludge as adsorbent in order to find what the best sludge activation mechanism In order that it submit a more efficient dye removal. The study is based initially on drying sludge, which was subsequently ground and sieved into different particle sizes. Then he underwent heat treatment followed by chemical treatments with sulfuric acid (H2SO4) 0.2 mol / L and ionic liquid 3- (1-methyl-3-imidazolium) propanesulfonate 0.006 mol / L. Based on experimental design performed, the best conditions for removal of dye Remazol Red RR occurred when the adsorbent was chemically treated with sulfuric acid and dye solution at pH 2.0, removing approximately 73% of dye present in the sample. The adsorbents were characterized by scanning electron microscopy (SEM), Spectroscopy Infrared Fourier Transform (FTIR) and Boehm method for determining the functional groups present on the surface, as well as analysis for determining the point of zero charge (pHPCZ) and physicochemical characterizations. The FTIR results obtained indicate that the adsorbents have functional groups comprising carboxylic acids; primary and secondary amines; alcohols and phenols; and alkane on its surface. Regarding kinetic studies it was found that the model that best fit the data was the pseudo second-order and balance studies indicate that the Langmuir isotherm model best described the behavior of the experimental data. Thus, it is concluded that it is possible to utilize the sewage sludge as an adsorbent for removal of coloring Remazol Red RR.